Internal Security Governance in Europe in the 21st Century: State, Civilizational Process and risk society (De Legibus - Law Journal, 2025)
This essay aims to contribute to the reflection on the evolution of governance, particularly since the Westphalian treaties in the 17th century, where (in)security emerges as a civilizational problem. In this sense, based on a qualitative approach, the evolution of internal security governance was analyzed, as a result of the civilizational process, through the dissection of the concept of security governance, the operative articulation of the concepts of civilizational process and risk society and the characterization of the meaning and theoretical scope of civilizational retrogression. The results show that we are heading towards a civilizational regression, given that the main pillars that constituted modern society - the constitution of social fields free of violence, the bonds of interdependence between citizens and be-tween states, network governance, the monopolization of the use of force by public guardianship, the dichotomy between internal security and national defence and, above all, the freedom – are under threat.
Keywords: Security Governance; Network Governance; Risk Society; Civilizational Process; Civilizational Setback.